The terrifying abyss of insignificance - Luke Billingham; Keir Irwin-Rogers (Oñati Socio-Legal Series)
The concept of mattering can be helpful for understanding the ways in which structural and historical factors affect individual psychologies. This paper lays out the usefulness of mattering as a lens through which to examine why a small minority of young people in Britain commit violent acts. We first explore what it means to matter and the evidence linking the quest to matter with violence, and then examine the factors in contemporary Britain which can diminish a young person’s sense of mattering, using recent community research. We then critique the British government’s attempt to address the problem of violence through Gang Injunctions and Knife Crime Prevention Orders. We conclude by suggesting that policy-makers could gain substantial insight from investigating the connections between marginalisation, mattering and violence, rather than focusing disproportionately on the music young people choose to listen to or create, or the specific weapon that they opt to carry.